Distinct cerebral cortical microstructural changes in idiopathic normal-pressure hydrocephalus - Hahm, Myong Hun; Jeong, Shin Young; Kim, Suhyun; Lee, Sang-Woo; Park, Ki-Su; Park, Eunhee; Eun, Mi-Yeon; Yoon, Uicheul; Kang, Kyunghun (Frontiers in Neurology, 2025)
ObjectiveThe aims of the study were to investigate differences in cortical mean diffusivity (MD) among idiopathic normal-pressure hydrocephalus (INPH) patients, Alzheimer’s disease (AD) patients, and healthy controls, and to analyze mean MD among INPH and AD groups in INPH-specific areas showing distinctive cortical MD changes for distinguishing INPH from AD.MethodsForty-two INPH patients, 51 AD patients, and 23 healthy controls were imaged with MRI, including diffusion tensor imaging MR images, for surface-based analysis across the entire brain.ResultsCompared with healthy controls, INPH patients showed a statistically significant reduction in MD in the high convexity of the frontal, parietal, and occipital cortical regions. We designate these clusters of lower MD as INPH MD LOW ROI. Additionally, a significant increase in MD, mainly in the ventromedial frontal cortex, ventrolateral frontal cortex, supramarginal gyrus, and temporal cortical regions, was observed in the INPH group relative to the control group. We designate these clusters of higher MD as INPH MD HIGH ROI. INPH patients showed significantly lower mean MD in INPH MD LOW ROI and higher mean MD in INPH MD HIGH ROI than AD. The mean MD of INPH MD LOW ROI had an AUC of 0.857 for differentiating INPH from AD.ConclusionA distinctive pattern of cortical MD changes was found in INPH patients, and cortical regions of low MD distinguished INPH from AD with good diagnostic sensitivity and specificity. Our findings suggest microstructural changes in cortical integrity can help differentiate INPH and AD in elderly patients.